Inulin-Type Fructan Supplementation of 3- to 6-Year-Old Children Is Associated with Higher Fecal Bifidobacterium Concentrations and Fewer Febrile Episodes Requiring Medical Attention. Issue 8 (3rd July 2018) - Lohner, Szimonetta; Jakobik, Viktória; Mihályi, Krisztina; Soldi, Sara; Vasileiadis, Sotirios; Theis, Stephan; Sailer, Manuela; Sieland, Carolin; Berényi, Károly; Boehm, Günther; Decsi, Tamás
Abstract: Background: Inulin-type fructans used in formula have been shown to promote microbiota composition and stool consistency closer to those of breastfed infants and to have beneficial effects on fever occurrence, diarrhea, and incidence of infections requiring antibiotic treatment in infants. Objectives: The primary study aim was to explore whether prophylactic supplementation with prebiotic fructans is able to influence the frequency of infectious diseases in kindergarten children during a winter period. A secondary objective was to ascertain the effect on the intestinal microbiota. Methods: 142 boys and 128 girls aged 3–6 y were randomly allocated to consume 6 g/d fructans or maltodextrin for 24 wk. At baseline, stool samples were collected for microbiota analysis and anthropometric measurements were made. During the intervention period diagnoses were recorded by physicians, whereas disease symptoms, kindergarten absenteeism, dietary habits, and stool consistency were recorded by parents. Baseline measurements were repeated at wk 24. Results: In total 219 children finished the study. Both the relative abundance of Bifidobacterium ( P  < 0.001) and that of Lactobacillus ( P  = 0.014) were 19.9% and 7.8% higher, respectively, post data normalization, in stool samples of children receiving fructans as compared with those of controls at wk 24. This was accompanied by significantly softer stools within the normal range in the prebiotic group from wk 12 onwards. The incidence of febrile episodes requiring medical attention [0.65 ± 1.09 compared with 0.9 ± 1.11 infections/(24 wk × child), P  = 0.04] and that of sinusitis (0.01 ± 0.1 compared with 0.06 ± 0.25, P  = 0.03) were significantly lower in the prebiotic group. The number of infectious episodes and their duration reported by parents did not differ significantly between the 2 intervention groups. Conclusions: Prebiotic supplementation modified the composition of the intestinal microbiota and resulted in softer stools in kindergarten-aged children. The reduction in febrile episodes requiring medical attention supports the concept of further studies on prebiotics in young children. This trial was registered at clinicaltrials.gov as NCT03241355.